45S5 Bioglass paste is capable of protecting the enamel surrounding orthodontic brackets against erosive challenge - Mona Aly Abbassy; Ahmed Samir Bakry; Nada Ibrahim Alshehri; Thoria Mohammed Alghamdi; Samiah Adnan Rafiq; Doha Hassan Aljeddawi; Danyah Saad Nujaim; Ali Habib Hassan (Wolters Kluwer Medknow Publications, 2019)
OBJECTIVES: This study aimed at evaluating the effect of using a 45S5 bioglass paste and a topical fluoride as protective agents against acidic erosion (resembling acidic beverage softdrinks intake) for enamel surrounding orthodontic brackets. MATERIALS AND METHODS: Sample of 21 freshly extracted sound incisor and premolar teeth was randomly divided into three equal groups: a bioglass group (Bioglass) (NovaMin, 5-mm average particle, NovaMin Technology), a Fluoride group (Fluoride) (Gelato APF Gel, Keystone Industries), and a control group (Control). Orthodontic brackets were bonded to the utilized teeth usingMIP (Moisture Insensitive Primer) and Transbond PLUS color change adhesive. All specimens were challenged by 1% citric acid for 18 min. The top enamel surfaces next to the orthodontic brackets were examined by SEM-EDS. Wilcoxon Signed-Rank test was used to compare the area covered by the 45S5 bioglass paste before/after erosion P < 0.05. RESULTS: 45S5 bioglass paste application resulted in the formation of an interaction layer that significantly resisted erosion challenge P < 0.05. The fluoride and control specimens showed signs of erosion of the enamel next to the orthodontic brackets (P < 0.05). CONCLUSION: 45S5 bioglass paste can efficiently protect the enamel surfaces next to orthodontic brackets for acidic erosion challenges.